Forage yield and accumulation of fertilized Marandu grass, intercropped with forage peanut or not fertilized under rotational grazing. - BERÇA, A. S. (2017)
The aims of this study were to evaluate the forage production and accumulation of marandu grass, intercropped with forage peanut (mixed) or fertilized with urea.